Servant-leadership as an effective model for teacher leadership - Giambattista Bufalino (Pensa MultiMedia, 2017)
This brief article aims to explore current approaches to teacher leadership in an attempt to advance its practice and energize the collective leadership of teachers. Leadership is not vested in one person who is assigned to a formal position of power or authority, but, rather, is a reciprocal process that enables participants in an educational community to construct meanings for a shared purpose of schooling. First, I acknowledge the teacher's role in leading improvement at both classroom and school levels. I, then, suggest that applying servant leadership to teacher leadership may serve as an opportunity to improve teaching practices.